RESEARCH OF EFFECT OF PLATELET RICH FIBRIN, PRF ON PARADONTOSIS TISSUES REGENERATION DURING THE EXPERIMENT - О. S. Barylo; Т. М. Kanishyna; А.V. Biloshytska (Український стоматологічний альманах)
The usage of Platelet Rich Fibrin, PRF means the possibility to apply growth factors in medicine.